2008
DOI: 10.1016/j.jhep.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Augmenter of liver regeneration: An important intracellular survival factor for hepatocytes

Abstract: Background/Aims-Augmenter of liver regeneration (ALR), a protein synthesized and stored in hepatocytes, is associated with mitochondria, and possesses sulfhydryl oxidase and cytochrome c reductase activities. We sought to determine the effects of ALR depletion in hepatocytes by antisense oligonucleotide transfection.Methods-Rat hepatocytes in primary culture were transfected with antisense oligonucleotide for ALR mRNA (ALR-AS) or scrambled oligonucleotide. Various analyses were performed at times up to 24 h af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 46 publications
(84 reference statements)
5
64
0
1
Order By: Relevance
“…33 The PI3K/ AKT and ERK pathways are also known to be important pathways for apoptosis. Although recent studies have reported anti-apoptotic effects of ALR in human hepatocytes, neuroblastoma cells, and hepatoma cells, [23][24][25][26] and rrALR has been shown to inhibit gentamicin-induced renal tubular cell apoptosis in vitro, 29 the mechanisms of ALR-inhibiting apoptosis remain unclear. Caspase-3 is the most important executioner in most apoptotic signaling cascades.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…33 The PI3K/ AKT and ERK pathways are also known to be important pathways for apoptosis. Although recent studies have reported anti-apoptotic effects of ALR in human hepatocytes, neuroblastoma cells, and hepatoma cells, [23][24][25][26] and rrALR has been shown to inhibit gentamicin-induced renal tubular cell apoptosis in vitro, 29 the mechanisms of ALR-inhibiting apoptosis remain unclear. Caspase-3 is the most important executioner in most apoptotic signaling cascades.…”
Section: Discussionmentioning
confidence: 97%
“…[20][21][22] Recent studies have shown that depletion of ALR in hepatocytes by anti-sense oligonucleotide transfection induced hepatocyte apoptosis, while recombinant human ALR (rhALR) significantly decreased hepatocyte apoptosis in vitro. 23,24 The expression of exogenous ALR increased the survival of hepatoma cells, accompanied by a decrease in apoptosis. 25 A protective effect of ALR on hydrogen peroxide-induced apoptosis in SH-SY5Y human neuroblastoma cells has also been found.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, inhibition of intracellular HSS expression by an antisense approach reduces cell survival against free radical insults, suggesting that HSS might be a cell survival factor (Thirunavukkarasu et al, 2008). In practice, administration of an HSS-bearing plasmid by hydrodynamic tail vein injection protects mice from hepatic failure, implying its potential role in clinical application.…”
Section: Introductionmentioning
confidence: 89%
“…HSS seems to have additional clinical implications because exogenous HSS administration to rats with thioacetamide-induced liver fibrosis/cirrhosis is able to significantly decrease fibrosis and suppress the onset of cirrhosis (Gribilas et al, 2009). ALR is critically important for the survival of hepatocytes because of its association with the maintenance of mitochondrial stability (Thirunavukkarasu et al, 2008). The results of our previous studies (Wu et al, 2007(Wu et al, , 2010Li et al, 2010) also demonstrated that the function of the HSS gene in liver cells may be related to its antiapoptotic effects, and the protective effect of HSS may be associated with the mitochondria via blockade of the mitochondrial permeability transition.…”
Section: Introductionmentioning
confidence: 99%
“…This was mainly due to the reduction of mitochondrial-mediated apoptosis characterized by ameliorated mitochondria membrane integrity, reduced cytochrome c release and enhanced ATP levels (23)(24)(25). In addition, downregulation of ALR expression using antisense oligonucleotide has demonstrated similar results in rat hepatocytes (26) and hepatoma cells (24) as well as a prosurvival role of ALR in the maintenance of murine embryonic stem cell pluripotency (27). Less is known about the regulation of ALR expression under conditions of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%